Pentagon Enterprise: helmet wiper & services helmet wiper / Nur Anis Izzatie Abdul Halim [et al.] - Abdul Halim, Nur Anis Izzatie; Abd Jalil, Nurain Nabilah Munawarah; Mohd Afendi, Nurizzati Hidayah; Zakaria, Nurfarhanah; Azmi, Nuraida Suraya; Abdul Mutalib, Halimatun Saidiah (2017)
Pentagon Enterprise sells helmet wipers which are used by motorcyclists to wipe their helmet screens during the heavy downpour. We decided to choose this kind of business because currently, in Malaysia, there is still no business that sells helmet wipers.